URGENCY OF GOVERNMENT REGULATION IN LIEU OF LAW AS AN EFFEVTIVIE SOLUTION TO ERADICATE CORRUPTION - Syafrizal Syafrizal (Indonesian Journal of Law and Policy Studies, 2021)
Corruption is an extra ordinary crime that harms the state, damages the nation's economy and hinders national development. Therefore, it is necessary to take extraordinary action in its eradication without having to consider human rights and customs that exist in society. One of the most important elements in eradicating corruption lies in the system of laws and regulations of a country, because in our country it is known that no act can be punished unless the law regulates it, so the urgency of issuing a Goverment Regulation il lieu of Law is very necessary to perfect the law. - the invitations that have been there. This research tries to analyze the substance in law Number 31 of 199 concerning the Eradication of Corruption Crime, in conjunction with Law 20 of 2001, Law Number 30 of 2002 in conjunction with law Number 19 of 2019 concerning the Corruption Eradication Commission by analyzing The phenomenon of corruption is increasing day by day, especially in terms of the mode and method of the perpetrators of hiding the results of the corruption. This study uses qualitative normative research with a statutory approach. The results of this study raise the substance that exists in Law Number 30 of 2002 in conjunction with Law Number 19 of 2019 concerning the Corruption Eradication Commission which needs to be refined or revised by issuing a new law that does not only rely on the actions that have been carried out by law enforcement but also preventive measures in a systematic way.